Schmidt number's impact during the growth of mc-silicon ingot through directional solidification furnace for photovoltaic applications: A computational investigation - T. Keerthivasan; M. Srinivasan; R. Madhesh; P. Ramasamy (Chemical Physics Impact, 2023)
The use of multi-crystalline silicon for photovoltaic solar cell applications is highly advantageous due to its low manufacturing costs. In this study, numerical simulations were conducted to investigate mass transport phenomena during the directional solidification of molten silicon for different Schmidt values at the critical Prandtl number of 0.01. The simulations were performed using the diffusion model and convection-conduction equations as the framework for the incompressible Navier-Stokes equation. The finite-volume method was used to carry out computations in a two-dimensional (2D) axisymmetric model. The diffusion flux of impurities (oxygen, carbon, and nitrogen) and dopants (phosphorus and boron) during the mc-silicon growth process was examined for Schmidt numbers Sc=0.5, Sc=5, and Sc=10. It was found that the Schmidt number Sc=0.5 is suitable for producing higher-grade mc-silicon ingots by regulating the production of impurities and dopants. The simulation results obtained in this study may provide a better understanding of the mc-silicon growth process and can be used to improve the production of high-quality mc-silicon ingots for photovoltaic applications.